액티브형 직접메탄올연료전지 시스템의 메탄올 농도 변동이 성능에 미치는 영향성에 대한 수치적 연구 - 곽건희(Geon Hui Gwak); 고요한(Jo Han Ko); 이수원(Su Won Lee); 이진우(Jin Woo Lee); 백동현(Dong Hyun Peck); 정두환(Doo Hwan Jung); 주현철(Hyun Chul Ju) (한국수소 및 신에너지학회 논문집, 2013)
In this study, we develop a one-dimensional (1-D), two-phase, transient-thermal DMFC model to investigate the effect of methanol concentration fluctuation that usually occurs in active-type direct methanol fuel cell (DMFC) systems. 1-D transient simulations are conducted and time-dependent behaviors of DMFCs are analyzed under various DMFC operating conditions such as anode/cathode stoichiometry, cell temperature, and cathode inlet humidification. The simulation results indicate that the effect of methanol concentration fluctuation on DMFC performance can be mitigated by proper control of anode/cathode stoichiometry, providing a guideline to optimize operating conditions of active DMFC systems.